The Effect Of Work Life Balance And Work Stress On Turnover Intention Through Job Satisfaction As An Intervening Variable On Generation Z Employees In Surabaya: English - Shofiyana Futri; Kustini Kustini (Cita konsultindo, 2024)
This study aims to prove the effect of Work Life Balance and Job Stress on Turnover Intention with Job Satisfaction as an Intervening Variable on Generation Z Employees in Surabaya. The sample of this study was 105 people with a sample determination using the Ferdinand formula. The data analysis technique in this study used Smart Pls. The results of the study showed that Work Life Balance had a negative and significant effect on Job Satisfaction, Work Stress had a negative and insignificant effect on Job Satisfaction, Work Life Balance had a negative and insignificant effect on Turnover Intention, Work Stress had a positive and significant effect on Turnover Intention, Job Satisfaction had a negative and insignificant effect on Turnover Intention, Work Life Balance had a positive and insignificant effect on Turnover Intention through Job Satisfaction, Work Stress had a positive and insignificant effect on Turnover Intention through Job Satisfaction.